Users' involvement in the innovation process through web 2.0: a framework for involvement analysis in a brazilian automotive company - Mazini, Sergio Ricardo [UNESP]; Gobbo, José Alcides [UNESP] (My University, 2015)
Organizations are inserted into a competitive environment in which innovation is an essential factor in gaining temporary competitive advantages. The search for external sources of knowledge, which can contribute to the innovation process, has become a constant among the organizations. One of the actors involved in this search is users, who often play an important role in the development of new products. This chapter develops a framework for the analysis of users’ involvement in the innovation process through Web 2.0. The research method used a unique case study conducted in a Brazilian automotive company that developed a project of a concept car involving users through Web 2.0. The presented study case was analyzed according to the framework. The obtained result shows that users can contribute not only with idea generation, but also with involvement in the innovation process, depending on which steps of the New Product Development (NPD) process they take part in. Moreover, increasingly users’ development, participation, and collaboration are essential factors in this process.